Needs Analysis for Developing STEM-PjBL-Based Student Worksheets to Support Creative Problem Solving in Alternative Energy Learning - Fatma Irma Sari; Kartini Herlina; Undang Rosidin; I Wayan Distrik; Ike Festiana (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Alternative energy learning in schools requires instructional materials that can connect scientific concepts with real-world problem solving. However, current learning practices are still often dominated by theoretical explanations, textbook-based instruction, and limited project-oriented activities. This study aimed to analyze physics teachers’ needs for developing STEM-PjBL-based student worksheets to support students’ Creative Problem Solving (CPS) in alternative energy learning. This study employed a descriptive survey method involving 27 physics teachers in Lampung Province. Data were collected using a teacher needs questionnaire and analyzed using descriptive statistics. The results showed that the teacher needs questionnaire was categorized as very valid, with an average validity percentage of 80.54%. In alternative energy learning, Problem Based Learning was the most frequently used learning model, while Project Based Learning was used by only 33.3% of teachers. Student worksheets and learning videos were the most commonly used learning resources, each used by 85.2% of teachers, while printed books were still used by 63.0% of teachers. Although 85.2% of teachers had used student worksheets and 59.3% had developed their own worksheets, only 48.1% reported using worksheets integrated with STEM-PjBL. Furthermore, 96.3% of teachers stated that they needed student worksheets designed to support students’ Creative Problem Solving. These findings indicate a gap between the availability of student worksheets and their integration with structured STEM-PjBL and CPS-oriented learning activities. Therefore, the development of STEM-PjBL-based student worksheets is needed to support more contextual, project-based, and problem-solving-oriented alternative energy learning.